2013
DOI: 10.3109/2000656x.2013.767202
|View full text |Cite
|
Sign up to set email alerts
|

Immediate two-stage tissue expander breast reconstruction compared with one-stage permanent implant breast reconstruction: A multi-institutional comparison of short-term complications

Abstract: Prosthesis-based techniques are the predominant form of breast reconstruction worldwide, with two-stage tissue expander procedures being the most popular. In the past decade, there has been increasing interest in performing single-stage implant reconstruction immediately following mastectomy as an attempt to simplify the reconstructive course and improve psychosocial morbidity. However, there is a paucity of large-scale, multi-institutional data comparing the outcomes of these two reconstructive strategies. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 22 publications
1
43
1
Order By: Relevance
“…1,5,28 In particular, the risks for implant loss and total complications were significantly higher in the one-stage group than those in the two-stage group. Davila The results of the aesthetic outcome analysis can be interpreted in the same context.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…1,5,28 In particular, the risks for implant loss and total complications were significantly higher in the one-stage group than those in the two-stage group. Davila The results of the aesthetic outcome analysis can be interpreted in the same context.…”
Section: Discussionmentioning
confidence: 88%
“…3 The other five studies did not describe the specific mastectomy types used, and they likely included cases of non-NSM. 1,4,19,23,26 Six studies compared patient demographics and operation-related characteristics between two groups. 1,[3][4][5]18,19 Of these, a study by Petersen et al 5 showed unilaterally unfavorable patient characteristics in which the one-stage group included a significantly higher rate of smokers and obese patients, which resulted in significant heterogeneity in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations